Politics and economy in small African island states: comparing Cabo Verde and São Tomé and Príncipe - Sanches, Edalina (2020)
The former Portuguese colonies of Cabo Verde and São Tomé and Príncipe are small African island states with fairly well-functioning democracies, but they represent different sides of the ‘small is beautiful’ debate. This chapter explores how and why democracy has been more consensual and stable in Cabo Verde and more conflict-prone and unstable in São Tomé and Príncipe, and why the former has managed to do a better job at improving socio-economic indicators than the latter. It starts by analysing the nature of party politics, elections and institutional relations between government and president, and then explores the presumed vulnerabilities and opportunities of economic development experienced by both states and how they have responded to these opportunities and challenges. The findings reveal the relevance of strong political institutions and international agency to understand the different pathways pursued by these small states.